Evolution of Helicobacter pylori susceptibility to antibiotics during a 10‐year period in Lithuania. Issue 5 (19th October 2012) - Kupcinskas, Limas; Rasmussen, Lone; Jonaitis, Laimas; Kiudelis, Gediminas; Jørgensen, Marianne; Urbonaviciene, Neringa; Tamosiunas, Vytas; Kupcinskas, Juozas; Miciuleviciene, Jolanta; Kadusevicius, Edmundas; Berg, Douglas; Andersen, Leif P.
<x xml:space="preserve">Abstract</x> The study evaluated the changes in the prevalence of Helicobacter pylori strains with primary resistance to antibiotics during the last 10 years in Lithuania. H. pylori susceptibilities to antibiotics were tested in 89 patients in 1998, in 81 patients in 2001 and in 90 patients in 2007/2008. Susceptibility to metronidazole, clarithromycin, amoxicillin and tetracycline was tested using E‐test or agar dilution method. Susceptibility to ciprofloxacin was only tested in 2007/2008. Data about utilization of all authorized and available on market macrolides and clindamycin in Lithuania during 2003–2007 were evaluated using WHO ATC/DDD methodology. A total of 260 H. pylori strains cultured from untreated adult patients were investigated. Primary resistance rates (1998, 2001 and 2007/2008) for metronidazole were 24.7%, 33.3%, and 35.6%, for clarithromycin 1.1%, 3.7%, and 3.3% and for tetracycline 0%, 2.5% and 0% respectively. No cases of amoxicillin resistance have been detected. The resistance rate for ciprofloxacin was 5.6% in 2007/2008. Data of total macrolides and clarithromycin utilization in Lithuania revealed that despite an increase of consumption of these drugs in Lithuania during 2003–2007 in 1.5 times, the total macrolide consumption remains one of the lowest in Europe. We have not observed any significant changes in the susceptibility of H. pylori to the most widely used antibiotics during the recent 10‐year period. The low resistance rate to clarithromycin might be related to the policy to avoid use of macrolides as first‐line treatment for pulmonary and other infections.